2010
DOI: 10.2147/jrlcr.s6504
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate pathway implication in amyotrophic lateral sclerosis: what is the signal in the noise?

Abstract: Abstract:The cause of the fatal motor neuron disease, amyotrophic lateral sclerosis (ALS), remains largely unknown. Most cases of ALS are sporadic and, for ∼20% of familial ALS patients, mutations in the superoxide dismutase-1 (SOD1) gene have been identified. Transgenic rodents overexpressing mutant SOD1 emulate the disease and constitute the best ALS animal model so far. Several lines of evidence suggest that ALS is a multifactorial condition. In this review, we discuss the question of the involvement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 253 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…In fact, although linkage between glutamate and neuroinflammation was suggested to have a role in potentiating MN death in a model mimicking ALS disease (Tolosa et al, 2011), other Authors have demonstrated that glutamate by itself was not able to induce MN damage in ALS (Tovar et al, 2009b). Indeed, it has been questioned the involvement of glutamate in ALS-induced MN death (Le Verche et al, 2011) and the cytotoxicity of the cerebrospinal fluid (CSF) from patients with ALS evidenced to not be related to glutamate (Gomez-Pinedo et al, 2013). …”
Section: Neurodegenerative Networking In Alsmentioning
confidence: 99%
“…In fact, although linkage between glutamate and neuroinflammation was suggested to have a role in potentiating MN death in a model mimicking ALS disease (Tolosa et al, 2011), other Authors have demonstrated that glutamate by itself was not able to induce MN damage in ALS (Tovar et al, 2009b). Indeed, it has been questioned the involvement of glutamate in ALS-induced MN death (Le Verche et al, 2011) and the cytotoxicity of the cerebrospinal fluid (CSF) from patients with ALS evidenced to not be related to glutamate (Gomez-Pinedo et al, 2013). …”
Section: Neurodegenerative Networking In Alsmentioning
confidence: 99%
“…A study found that overexpression of GLT-1 in the cervical spinal cord of SOD1G93A mice with ALS did not protect motor neurons, preserve diaphragm function, or prolong animal survival, thus challenging the notion that EAAT2 is a primary factor in motor neuron degeneration in ALS [249]. It is thought that simultaneous targeting of calcium overload, endoplasmic reticulum stress, and mitochondrial dysfunction pathways may be necessary to halt ALS progression [250].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%